Antioxidant Activity of Isoflavones and Biflavones Isolated from Godoya antioquiensis - Benedek, Birgit; Weniger, Bernard; Parejo, Irene; Bastida, Jaume; Arango, Gabriel Jaime; Lobstein, Annelise; Codina, Carles (Arzneimittelforschung, 2006)
Two biflavones, ochnaflavone (1) and 2'',3''-dihydroochnaflavone (2), and two isoflavones, 5,7,4'-trihydroxy-3',5'-dimethoxyisoflavone (piscigenin) (3) and 5,4'-dihydroxy-7,3',5'-trimethoxyisoflavone (4), a new natural compound, were isolated from the leaves of Godoya antioquiensis (Ochnaceae). Their structures were determined on the basis of spectral data and by comparison with data reported in the literature. The isolated compounds were evaluated for their radical scavenging activity using the NBT (nitrobluetetrazolium)/hypoxanthine superoxide and the ·OH/luminol chemiluminescence methods. The isolated isoflavones were found to exhibit a strong hydroxyl radical scavenging activity and a moderate inhibition of the superoxide anion, whereas the two biflavones were inactive in the superoxide anion assay and showed a low hydroxyl radical scavenging activity.
Keywords: Antioxidants; Biflavones,antioxidant activity; Godoya antioquiensis; Isoflavones,isolation; Ochnaceae